Model Pembelajaran Scramble Terhadap Kemampuan Pemecahan Masalah IPA Ditinjau Dari Cognitive Style Siswa Sekolah Dasar - Wardana, Dina Rahma; Irianto, Apri; Rachmadtullah, Reza (EduBase : Journal of Basic Education, 2023)
The development of learning models can be adapted to the conditions and needs of the learning process so that the atmosphere in the class is not easily bored, students quickly receive learning material and improve cognitive learning styles in solving student problems. This research is a quantitative study with a Quasi Experimental Post-test Only Control Group Design. Participants were 21 students in each class IV-A and IV-B. The data collection technique was in the form of a HOTS question description test after being treated (having carried out the learning process using the scramble method) and the results of observations regarding students' cognitive style ( Field Independent and Field Dependent). Data analysis techniques used the normality test, homogeneity test and hypothesis testing with the help of SPSS version 25. The results showed that (1) there was an influence of the Scramble learning model on the problem solving abilities of science subjects seen from the Cognitive Style of elementary school students (2) Cognitive Style was effective in the scramble learning model because there is an interaction between the scramble learning model and cognitive style on the problem solving abilities of fourth grade students in science subjects. Thus it can be concluded that "There is an Influence of the Scramble Learning Model on the Ability to Solve Problems in Science Subjects Viewed from the Cognitve Style of Elementary School Students".